Elements for an environmental foreign policy - Salvador, Iñigo (2016)
The need for an environmental foreign policy in Ecuador derives from the global character of environmental issues, the country's responsibility towards its privileged mega diversity, the unavoidable link between poverty and environmental degradation as well as from international commitments. While an environmental foreign policy must be centrally commanded by a government agency, it should be designed through a participatory process capable of engaging all the actors who are actually involved in environmental issues. This article suggests several concrete themes that should be part of the Ecuadorian environmental international agenda.